2009
DOI: 10.4049/jimmunol.0801699
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Seropositivity in Childhood Associates with Decreased Monocyte-Induced NK Cell IFN-γ Production

Abstract: EBV infection is inversely associated with IgE sensitization in children, and this association is further enhanced by CMV coinfection. In mice, herpesvirus latency causes systemic innate activation and protection from bacterial coinfection, implying the importance of herpesviruses in skewing immune responses during latent infection. Early control of viral infections depends on IFN-γ release by NK cells, which generally requires the presence of accessory cells. We investigated IFN-γ production by NK cells in PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 60 publications
0
31
0
1
Order By: Relevance
“…Owing to the asymptomatic presentation of EBV during infancy, little is known regarding the course of infection in children of different ages. Our previous studies indicated that the time point of EBV acquisition during early childhood, and the occurrence of coinfection with CMV, might affect immunomodulation by the virus (4,29). In this study, we show in an in vitro-based infection system that a child's age and serostatus to CMV, and subsequent ability to mount IFN-g responses, affect EBV-induced activation and expansion of B cells.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Owing to the asymptomatic presentation of EBV during infancy, little is known regarding the course of infection in children of different ages. Our previous studies indicated that the time point of EBV acquisition during early childhood, and the occurrence of coinfection with CMV, might affect immunomodulation by the virus (4,29). In this study, we show in an in vitro-based infection system that a child's age and serostatus to CMV, and subsequent ability to mount IFN-g responses, affect EBV-induced activation and expansion of B cells.…”
Section: Discussionmentioning
confidence: 71%
“…Our group has found that latency with EBV and CMV influenced functional responses of T and NK cells and that these responses differed in children coinfected with both viruses compared with those with EBV alone (29,30). Furthermore, the time point of primary EBV infection during early childhood appeared important for EBV-induced modulation of immune responses (4).…”
Section: E Pstein-barr Virus Infection Is Commonly Contracted Inmentioning
confidence: 99%
“…To our knowledge, however, no studies have yet focused on the possible synergistic role of EBV and CMV coinfection on antiviral effector cell maturation. Notably, earlier studies from our group have suggested a synergistic protective effect of EBV and CMV coinfection against IgE sensitization (24), and distinct modulation of NK cell gamma interferon (IFN-␥) production capacity by the two viruses (25). This raises the intriguing possibility of in vivo interplay of CMV and EBV latency and that this interplay may have a functional imprint on subsequent immune responses early in life.…”
Section: Nkg2cmentioning
confidence: 94%
“…To understand whether herpesvirus carriage also associated with priming the NK cell function in humans, we induced NK cell activation through different pathways in PBMC from a group of children. We used K562 and Daudi target cells to induce activation via NK cell receptors, anti-CD16 antibodies to induce antibodydependent cell-mediated cytotoxicity, and the addition of peptidoglycan (a Toll-like receptor 2 agonist), together with IL-15, to mimic accessory cell-mediated NK cell activation (25).…”
Section: Nk Cells From CMVmentioning
confidence: 99%
“…Although some of this is heterogeneity may be genetically determined and/or stochastic, 37 exposure to infections in addition to HCMV may also affect NK cell maturation. 7,15,17,56 Further studies are needed to determine whether this is simply a cytokine-driven expansion, and thus likely to occur in response to many acute inflammatory stimuli, or whether some pathogens express specific ligands for CD57…”
mentioning
confidence: 99%